How To Apply Resfecfull Midwifery Care In Improving The Quality Of Midwifery Services? - Petralina, Bintang; Handayani, Lutfi; Larasati, Eggy Widya (Jurnal Bidan Cerdas, 2024)
Introduction: Midwives play a strategic role in shaping future generations and ensuring women's reproductive and sexual health. Every woman and newborn has the right to quality care and a positive birthing experience, which is best achieved through Respectful Midwifery Care (RMC). Method: This systematic review, conducted according to PRISMA guidelines, aims to explore the relationship between RMC and the improvement of midwifery service quality. Keywords such as “respectful midwifery care,” “women's empowerment,” “antenatal care,” “childbirth,” “family support,” and “pregnancy” were utilized. Out of 86 identified articles, 30 studies met the inclusion criteria. Results: The review included studies from various regions, examining characteristics like publication details, research design, and location. The findings consistently show a strong correlation between RMC practices—focused on women's empowerment, family support, and positive birthing experiences—and enhanced quality of midwifery services. Conclusion: The implementation of RMC, with an emphasis on empowerment and family involvement, significantly improves midwifery service quality. This review of 30 eligible studies from diverse global settings underscores the widespread effectiveness of RMC across different contexts.